Fire in the iron horse : trains in British literature 1848-1906 - Wee, Steffi Heloise (Nanyang Technological University, 2020)
After decades of playing second fiddle to cars and planes, trains seem to be making a comeback in Europe. In the UK, steam trains joyrides have risen in popularity, with famous locomotives like The Flying Scotsman bringing out the crowds. However, as their popularity increases it becomes harder to ignore the nationalistic and nostalgia implications of steam trains, and how deeply they were intertwined with empire or industrialism. This essay will use notable Victorian and Edwardian pieces of literature to explore what made trains such a British icon and how the romanticism of it has affected the industry over time.